Türkiye İllerinin Bilgi Kenti Olma Potansiyelinin Ölçülmesi - Kaçar, Sinem Metin (Fen Bilimleri Enstitüsü, 2016)
Change in production systems has effected urban form, society classes and lifestyles throughout the history of human kind. As a result of the developments in information and communication technologies (ICT) added a commercial value to new and scientific knowledge and what-so-called knowledge economy has evolved into our lives. The difference in knowledge-based production systems from commodity based production systems raised the importance of knowledge production, sharing, diffusion and spillover in economy-development dilemma. The hand-in-hand relationship of city, economy and society resulted with the necessity of a new urban theory, Knowledge City. It is commonly accepted that Knowledge City supports competitiveness and innovation in the context of knowledge economy and Knowledge-Based Urban Development (KBUD) strategies that provides a pathway to become a Knowledge City has recently started to be implemented all around the world. KBUD strategies provides a comprehensive approach that does not only provide economic and urban goals; but also, requires social and intitutional strategies. Knowledge worker, who is the common ground of knowledge economy and Knowledge City and defined as the part of the society that produces, uses and shares new knowledge, is at the top of the list of KBUD strategies. The first step of development strategies for a city, region and/or country is to attract and sustain knowledge worker. The reflection of these fast developments on developing countries, who do not produce technical and scientific knowledge, can create limitations on policies and implementations. The main objective of the thesis is to evaluate the economy-city relationship under the new dynamics of knowledge economy from developing countries’ perspective. Based on the literature and implementations of Knowledge City, the research question of "Should Turkey develop a Knowledge City to support knowledge economy?" was raised in the light of what indicators can be used to measure Knowledge City potential for Turkey and which cities have higher potential of these indicators under the scope of identified problem and goal and the model to determine the cities with higher potential to become a Knowledge City was proposed and the results were presented. The goals of the study are to contribute to the liteature in knowledge economy and Knowledge city relationship and the conceptual frameworks, to evaluate the development process of the selected Knowlege Cities in the world, to commentate Knowledge City and KBUD the assessment models to develop a model for Turkey and to measure the potential of Turkey’s 81 provinces’ to become a Knowledge City. The thesis contribute to future studies on the cities with higher potential to become Knowledge Cities and to determine strengths and weaknesses in sub-indices and variables. Thus, the thesis is expected to shed light to the formation of urban development strategies and to use national resources wisely. The results of the thesis indicate that Turkish provinces have very low potential comparing with world standards. Generally in the nation, there is a considerable similarity between the socio-economic development level and the Knowledge City potential. Istanbul is the city with the highest potential of becoming a Knowledge City in Turkey. However, the literature and examples from the world indicates that Istanbul’s role as a global city and finance capital prevent it to become a successful Knowledge City. Therefore, this thesis recommends to study cities with high potential, Ankara, İzmir and Bursa, in future studies.

Change in production systems has effected urban form, society classes and lifestyles throughout the history of human kind. As a result of the developments in information and communication technologies (ICT) added a commercial value to new and scientific knowledge and what-so-called knowledge economy has evolved into our lives. The difference in knowledge-based production systems from commodity based production systems raised the importance of knowledge production, sharing, diffusion and spillover in economy-development dilemma. The hand-in-hand relationship of city, economy and society resulted with the necessity of a new urban theory, Knowledge City. It is commonly accepted that Knowledge City supports competitiveness and innovation in the context of knowledge economy and Knowledge-Based Urban Development (KBUD) strategies that provides a pathway to become a Knowledge City has recently started to be implemented all around the world. KBUD strategies provides a comprehensive approach that does not only provide economic and urban goals; but also, requires social and intitutional strategies. Knowledge worker, who is the common ground of knowledge economy and Knowledge City and defined as the part of the society that produces, uses and shares new knowledge, is at the top of the list of KBUD strategies. The first step of development strategies for a city, region and/or country is to attract and sustain knowledge worker. The reflection of these fast developments on developing countries, who do not produce technical and scientific knowledge, can create limitations on policies and implementations. The main objective of the thesis is to evaluate the economy-city relationship under the new dynamics of knowledge economy from developing countries’ perspective. Based on the literature and implementations of Knowledge City, the research question of "Should Turkey develop a Knowledge City to support knowledge economy?" was raised in the light of what indicators can be used to measure Knowledge City potential for Turkey and which cities have higher potential of these indicators under the scope of identified problem and goal and the model to determine the cities with higher potential to become a Knowledge City was proposed and the results were presented. The goals of the study are to contribute to the liteature in knowledge economy and Knowledge city relationship and the conceptual frameworks, to evaluate the development process of the selected Knowlege Cities in the world, to commentate Knowledge City and KBUD the assessment models to develop a model for Turkey and to measure the potential of Turkey’s 81 provinces’ to become a Knowledge City. The thesis contribute to future studies on the cities with higher potential to become Knowledge Cities and to determine strengths and weaknesses in sub-indices and variables. Thus, the thesis is expected to shed light to the formation of urban development strategies and to use national resources wisely. The results of the thesis indicate that Turkish provinces have very low potential comparing with world standards. Generally in the nation, there is a considerable similarity between the socio-economic development level and the Knowledge City potential. Istanbul is the city with the highest potential of becoming a Knowledge City in Turkey. However, the literature and examples from the world indicates that Istanbul’s role as a global city and finance capital prevent it to become a successful Knowledge City. Therefore, this thesis recommends to study cities with high potential, Ankara, İzmir and Bursa, in future studies.
Measuring The Potential Of Turkish Provinces To Become Knowledge Cities
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (PhD) -- İstanbul Technical University, Institute of Science and Technology, 2016
Keywords: Ekonomik Coğrafya; Bilgi Kenti; Bilgi Ekonomisi; Bilgi Toplumu; Türkiye; Economic Geography; Knowledge City; Knowledge Economy; Knowledge Worker; Turkey